(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The interaction of electromagnetic fields (EMFs), particularly the oscillating magnetic field (OSMF), and living things has recently received a lot of attention. Despite the fact that the effects of EMFs on numerous physiological systems have been thoroughly studied, there has been little research on the potential effects of EMFs on kidney parameters in the context of malaria parasite infection. This study looked at how EMF (OSMF) exposure affected kidney parameters in mice infected with malaria parasites. Mice infected with Plasmodium berghei were randomly divided into five EMF-exposed groups (10mT, 15mT, 20mT, 30mT, and 40mT) and four control groups (Treatment control, Negative control, Positive control, and Normal control). The Treatment control group was not infected but was exposed to 40mT EMF, while the Negative control group was infected and exposed to 40mT EMF, The negative control group was infected but not treated, whereas the positive control group received antimalarial treatment (arthemether lumenfantrine). The Normal control group was not infected and was not treated. The EMF-exposed groups were exposed to a 50 Hz electromagnetic field of varying magnitudes for six hours per day for five days. After five days of EMF exposure, the EMF-exposed and control groups were sacrificed, and their kidney tissues were collected for analysis. The conventional biomarkers for kidney function, serum creatinine and blood urea nitrogen, were measured. In addition, parasite density was determined. In mice infected with the malaria parasite, results show that EMF exposure significantly altered kidney parameters. The EMF-exposed group had higher levels of blood urea nitrogen than the control groups.